Association of serum pepsinogens and gastrin-17 with Helicobacter pylori infection assessed by urea breath test - Zhou, Jun-peng; Liu, Chang-hai; Liu, Bo-wen; Wang, You-juan; Benghezal, Mohammed; Marshall, Barry James; Tang, Hong; Li, Hong (Frontiers in Cellular and Infection Microbiology, 2022)
Background Association of gastric atrophy or cancer with levels of serum pepsinogens, gastrin-17 and anti-Helicobacter pylori IgG antibody have been extensively studied. However, the association of serum pepsinogen and gastrin-17 with H. pylori infection has not been studied in a large population. Aim To investigate the impact of H. pylori infection on serum levels of pepsinogens and gastrin-17. Methods A total of 354, 972 subjects who underwent health check-ups were included. Serum levels of pepsinogens and gastrin-17 were measured using the enzyme-linked immunosorbent assay. H. pylori infection was detected using 14C-urea breath test (UBT). Multivariable logistic regression analysis was used to investigate the association of serum pepsinogen and gastrin-17 with H. pylori infection. Results H. pylori prevalence was 33.18% in this study. The mean levels of pepsinogens and gastrin-17 were higher, while the mean pepsinogen-I/II ratio were lower among H. pylori-positive than -negative subjects. In H. pylori-positive subjects, pepsinogen and gastrin-17 levels correlated positively, whereas the pepsinogen-I/II ratio correlated negatively with UBT values (e.g., the mean serum level of pepsinogen-I in subjects with UBT values in the range of 100-499dpm, 500-1499dpm, and ≥1500dpm was 94.77 ± 38.99, 102.77 ± 43.59, and 111.53 ± 47.47 ng/mL, respectively). Compared with H. pylori-negative subjects, the adjusted odds ratio (aOR) of having pepsinogen-I ≤ 70 ng/mL in the three H. pylori-positive but with different UBT value groups was 0.31 (p<0.001), 0.16 (p<0.001), and 0.08 (p<0.001), respectively; while the aOR of having G-17>5.70 pmol/L was 4.56 (p<0.001), 7.43 (p<0.001), and 7.12 (p<0.001). This suggested that H. pylori-positive subjects with higher UBT values were less likely to have pepsinogen-I ≤70 ng/mL (a serum marker for gastric atrophy), but more likely to have gastrin-17 >5.70 pmol/L (a marker for peptic ulcer). Conclusions H. pylori-positive subjects with higher UBT values are unlikely to have gastric atrophy, but may have greater risk of severe gastritis or peptic ulcers. Our study suggests that H. pylori-positive patients with high UBT values may benefit the most from H. pylori eradication.